1997
DOI: 10.1242/dev.124.14.2807
|View full text |Cite
|
Sign up to set email alerts
|

The bicoid-related homeoprotein Ptx1 defines the most anterior domain of the embryo and differentiates posterior from anterior lateral mesoderm

Abstract: Ptx1 is a member of the small bicoid family of homeobox-containing genes; it was isolated as a tissue-restricted transcription factor of the pro-opiomelanocortin gene. Its expression during mouse and chick embryogenesis was determined by in situ hybridization in order to delineate its putative role in development. In the head, Ptx1 expression is first detected in the ectoderm-derived stomodeal epithelium at E8.0. Initially, expression is only present in the stomodeum and in a few cells of the rostroventral for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…To date, three Ptx genes have been cloned from various species (reviewed in Drouin et al, 1998a,b;Gage et al, 1999): Ptx1 (Pitx1) (Lamonerie et al, 1996;Muccielli et al, 1996;Szeto et al, 1996;Shang et al, 1997;Vorbruggen et al, 1997), Ptx2 also known as Pitx2 or Otlx2 (Muccielli et al, 1996;Semina et al, 1996;Gage and Camper, 1997) and Ptx3 (Semina et al, 1997;Smidt et al, 1997). Ptx1, the founding member of this family, was cloned initially as a regulator of pro-opiomelanocortin (POMC) gene expression in pituitary corticotrope cells (Lamonerie et al, 1996), but was later found to be a pan-pituitary regulator of transcription (Tremblay et al, 1998) and to be required for mandible and hindlimb development (Lancto ˆt et al, 1999b;Szeto et al, 1999) in agreement with its expression during development (Lancto ˆt et al, 1997). Ptx2 was first identified as the causative gene for Rieger's syndrome (Semina et al, 1996) and it was recently shown to be an effector for development of left-right asymmetry of lateral mesoderm plate derivatives such as heart and stomach (Logan et al, 1998;Piedra et al, 1998;Ryan et al, 1998;Yoshioka et al, 1998;Campione et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three Ptx genes have been cloned from various species (reviewed in Drouin et al, 1998a,b;Gage et al, 1999): Ptx1 (Pitx1) (Lamonerie et al, 1996;Muccielli et al, 1996;Szeto et al, 1996;Shang et al, 1997;Vorbruggen et al, 1997), Ptx2 also known as Pitx2 or Otlx2 (Muccielli et al, 1996;Semina et al, 1996;Gage and Camper, 1997) and Ptx3 (Semina et al, 1997;Smidt et al, 1997). Ptx1, the founding member of this family, was cloned initially as a regulator of pro-opiomelanocortin (POMC) gene expression in pituitary corticotrope cells (Lamonerie et al, 1996), but was later found to be a pan-pituitary regulator of transcription (Tremblay et al, 1998) and to be required for mandible and hindlimb development (Lancto ˆt et al, 1999b;Szeto et al, 1999) in agreement with its expression during development (Lancto ˆt et al, 1997). Ptx2 was first identified as the causative gene for Rieger's syndrome (Semina et al, 1996) and it was recently shown to be an effector for development of left-right asymmetry of lateral mesoderm plate derivatives such as heart and stomach (Logan et al, 1998;Piedra et al, 1998;Ryan et al, 1998;Yoshioka et al, 1998;Campione et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Ptx2 was first identified as the causative gene for Rieger's syndrome (Semina et al ., 1996) and it was recently shown to be an effector for development of left–right asymmetry of lateral mesoderm plate derivatives such as heart and stomach (Logan et al ., 1998; Piedra et al ., 1998; Ryan et al ., 1998; Yoshioka et al ., 1998; Campione et al ., 1999). Expression of Ptx1 and Ptx2 is detected in the stomodeum at embryonic day 8 (E8) and, subsequently, is maintained in all stomodeal derivatives, including Rathke's pouch, the pituitary anlage (Muccielli et al ., 1996; Lanctôt et al ., 1997; 1999a). Thus, Ptx1 and Ptx2 represent the earliest known markers of pituitary organogenesis and may have redundant activity in this tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these two structures also share homologues of important otic genes like Pax2/8 that are expressed within the atrium of ascidians [127,250]. Hatschek's pit also shares expression of Pitx with Rathke's pouch, further supporting a potential evolutionary origin of these placodes [25,74,134,265].…”
Section: Evolutionary Origins and Differences Among Taxamentioning
confidence: 87%
“…We used the seqFISH data pre-processed by Squidpy (Palla et al, 2022a;Data ref: Palla et al, 2022b). After defining immediate neighbors using Delaunay triangulation (Delaunay, 1934) (Lanctôt et al, 1997;Chung et al, 2010;Tran & Kioussi, 2021).…”
Section: Cellneighborex Categorizes Transcriptome To Investigate the ...mentioning
confidence: 99%